Network slice technology in 5G radio access network - Yi WANG; Fengya LUO; Guolin SUN (Dianxin kexue)
As a core content in SDN(software defined networking) technical framework,network slice has become a key technology in 5G network evolving processing.In the meanwhile,radio resource management should be focused on virtulized resource and sliced design in the RAN(radio access network),which is being confronted with much more ubiquitous access in 5G evolution.Based on the technical demand and function scenario definition for network slicing in RAN management,the states of the art in radio resource management were discussed,and moreover,the challenges in RAN design were also proposed,which would perform references for the future research.